2021
DOI: 10.17770/sie2021vol2.6350
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family and Individual Factors on 4th Grade Students’ Self-Confidence in Reading Literacy: Results From Pirls 2016

Abstract: The self-confidence of a child and an adult is associated with performance and achievement results. It is well-studied, and the correlation has been proved that higher self-efficacy leads to higher achievements and performance, including better performance in reading literacy. It is also known that both a family and a home environment have a tremendous impact on the child’s development and academic performance. This article focuses on the 4thgraders and their family factor impact on the development of a child’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…It has been found in the IEA's (International Association for the Evaluation of Educational Achievement) and other educational studies, that students' achievement is strongly related to their background information. Geske and colleagues (Geske et al, 2021a) found that reading achievement and students' self-confidence correlation coefficient is up to 0.50 and reading achievement explains up to 25% of students' reading self-confidence (Geske et al, 2021b) at the 4th grade, if the achievement is analyzed together with students liking the subject and engagement, this model explained even up to 57% of confidence variance (Kampmane & Ozola, 2022). Marsh and O'Mara (2008) proved that academic confidence predicted long-term academic attainment better than school grades, IQ, and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found in the IEA's (International Association for the Evaluation of Educational Achievement) and other educational studies, that students' achievement is strongly related to their background information. Geske and colleagues (Geske et al, 2021a) found that reading achievement and students' self-confidence correlation coefficient is up to 0.50 and reading achievement explains up to 25% of students' reading self-confidence (Geske et al, 2021b) at the 4th grade, if the achievement is analyzed together with students liking the subject and engagement, this model explained even up to 57% of confidence variance (Kampmane & Ozola, 2022). Marsh and O'Mara (2008) proved that academic confidence predicted long-term academic attainment better than school grades, IQ, and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found in the IEA's (International Association for the Evaluation of Educational Achievement) and other educational studies, that students' achievement is strongly related to their background information. Geske and colleagues (Geske et al, 2021a) found that reading achievement and students' self-confidence correlation coefficient is up to 0.50 and reading achievement explains up to 25% of students' reading self-confidence (Geske et al, 2021b) at the 4th grade, if the achievement is analyzed together with students liking the subject and engagement, this model explained even up to 57% of confidence variance (Kampmane & Ozola, 2022). Marsh and O'Mara (2008) proved that academic confidence predicted long-term academic attainment better than school grades, IQ, and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have found that factors such as parental support [6] and quality of ESL instruction [7] can enhance literacy skills. For example, Caravolas [7] submitted that it is possible for ESL learners to not be able to transfer acquired literacy skills in their first language to the target language because of the differences in orthographies.…”
Section: Introductionmentioning
confidence: 99%
“…Phonics instruction has been reported to be effective at improving proficiency in literacy skills and reading comprehension among pupils in elementary school [16,17];. Other studies have investigated the influence of parental involvement on the development of literacy skills in young readers [6]. Parental involvement includes all the actions carried out by parents to support the pupils at school regarding the acquisition of literacy skills.…”
Section: Introductionmentioning
confidence: 99%